English-Language Media Coverage of the Two Olympics Under the Threat of the Pandemic - Xiaoling Zhang; Gareth Shaw (Journal of Current Chinese Affairs)
The paper aims to reveal how the two Olympic Games (the delayed Tokyo 2020 Olympic Games in July 2021 and the Beijing Winter Olympics in January 2022) were reported, that is, if, how, and why sentiment expressed towards the two hosting countries differs, and the implications. We conducted a study of 108 articles from six English-language news media publications to uncover repeated patterns of representations that may lead readers to form a preferred reading and interpretation of the two nations through the lens of COVID-19 and the shared international experience of sporting competitions. To understand how their representations were formed and worked, we turned to Said's Orientalism and the related notion of “the Other.” We hope the study will contribute not only to a more nuanced understanding of the rising anti-Asian sentiment in the West, but also to the theorisation of the evolving notion of Orientalism, especially during the pandemic period.